Security of Personal Data on Internet of Things Using AES - Shakil, Sadiya; Singh, Vineet (International Journal of Computer Sciences and Engineering, 2025)
This paper includes the process of implementing cryptographical rule on the idea of AES. As Cryptography is that method of changing plaintext into cipher text changing keys to secure our personal knowledge. While to provide a system with security services comes at the expense of system performance.IOT devices area unit connected to internet of things. This paper deal with the implementation of AES using Internet of things and the motive is to find the elapsed time of encryption and decryption by enhancing the key generation of AES. IOT is network of physical objects, device, vehicles building. So The paper contributes the analysis of the performances of AES algorithm. AES is one of the standardized high security rule. it's enforced in varied hardware devices and varied code languages. This paper explores the implementation of AES in MATLAB. A MATLAB code is developed for plaintext encoding and cipher text decipherment.. The elapsed time will be calculated for comparing the performances of file sizes. Hence the result will show how the file size is effecting the performance of elapsed time and plotting of the graph will show the evaluation in diagrammatic forms.